Pengaruh Ukuran Perusahaan, Kebijakan Dividen dan Opini Audit Terhadap Harga Saham - Abdurohman, Muhamad; Indra, Jasmi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The study aims to determine the impact of corporate size, dividend policies and audit opinions on the share price of IDX30 companies listed on the Indonesian Stock Exchange in 2018-2022. The type of research used is quantitative using secondary data. The population in this study is all IDX30 stock index companies listed on the Indonesian Stock Exchange in the period 2018 to 2022. The sample selection was done using the Purposive Sampling method, with samples obtained by 14 (fourteen) companies. The data analysis technique used is panel data regression. With data processing using the EVIEWS 10 program. The results showed that the size of the company, the dividend policy and the audit opinion simultaneously influenced the price of the stock.